Sensitivity to the Regularity of Letter Patterns Within Print Among Preschoolers: Implications for Emerging Literacy. Issue 4 (2nd October 2018) - Mano, Quintino R.; Kloos, Heidi
ABSTRACT: When learning to read, the developing mind is likely to cluster letters into frequency-based chunks. In the current study, the authors investigated the extent to which such chunking takes place among preschoolers ( N = 54) by examining the association between sensitivity to subword orthographic regularity and preschooler age. A version of the wordlikeness judgment paradigm was administered to assess sensitivity to the frequency of particular grain sizes (unigram, bigram, and trigram), regardless of their positional frequency within words. The task manipulation affected bigram performance but not unigram or trigram performance and was observed only among older preschoolers. Results suggest that preschoolers first become sensitive to bigram frequency. The special status of bigrams within subword frequency sensitivity, over and above unigrams and trigrams, has practical implication for reading instruction and remediation.